Responsible mining : case studies in managing social and environmental risks in the developed world - Jarvie-Eggart, Michelle E. (Society for Mining Metallurgy and Exploration (SME), 2015)
Mining Can Be Environmentally and Socially Responsible-and Still Profitable Even in this regulated, environmentally aware world, running a mine can be done safely, with combined goals of maximizing both the return on investment from extraction and the positive environmental and social impact that a well-run, responsible mine can offer. Responsible Mining is your comprehensive guide to addressing social and environmental risks at mines in the developed world. This book gathers case studies of best practices across the full range of issues. With examples from four continents, you can learn from.